(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2013)
A high performance liquid chromatographic method for determination of rifabutin in human plasma was developed. The method involved deproteinisation of the sample with acetonitrile and analysis of the supernatant using a reversed-phase C18 column (250mm) and UV detection at a wavelength of 265nm. The assay was specific for rifabutin and linear from 0.025 to 10.0μg/ml. The relative standard deviation of intra- and inter-day assays was lower than 10%. The method was able to remove interfering materials in plasma, yielding an average recovery of rifabutin from plasma of 101%. Due to its simplicity, the assay can be used for pharmacokinetic studies of rifabutin. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS; 2012; IX(2) 26-29 DOI: http://dx.doi.org/10.3126/saarctb.v9i2.7975